Limits on C and P violation in gravitation from SN 1987A data - Almeida, L. D. [UNESP]; Matsas, G. E.A. [UNESP]; Natale, A. A. [UNESP] (American Physical Society (APS), 1989)
We show that the analyses of Longo and Krauss and Tremaine which determine limits on the equivalence principle from SN 1987A data can be used to constrain the existence of C and P violation in gravitation. © 1989 The American Physical Society.